KEUNGGULAN DINAR DIRHAM SEBAGAI ALAT TUKAR - Sri Maharani (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2023)
Trade is a buying and selling transaction between a seller and a buyer that has occurred since prehistoric times, this is done by exchanging goods and services because at that time there was no known currency as a medium of exchange. The need for a medium of exchange that is acceptable to everyone and is flexible is needed. Apart from being a medium of exchange, money also functions as a measure that can be used to value goods or services. Including the blessings of Allah SWT is the creation of dinars and dirhams with both life being straight. The definition of the Dinar is a piece of gold that is printed and measured by the mitsqol scales and the dirham is between the coins made of silver. Islam views that the currency (medium of exchange) in Islam is dinar (gold) and dirham (silver). There is a necessity to make the dinar and dirham as standard currencies in the Islamic economic system. The advantages of the dinar dirham as a medium of exchange include: the dinar and dirham currencies have very strong legitimacy both domestically and abroad, dinars and dirhams made of gold and silver high value and widely accepted by the world community, currencies based on the dinar and dirham also have monetary advantages, one: low and controlled inflation, two: in the gold standard, the exchange rate between countries is relatively stable because the currencies of each country are relied on. on gold which is stable in value, three: the dinar and dirham system will create a balance of payments between countries automatically, to correct the difference in payments without central bank intervention, four: the dinar and dirham system has a very prime advantage, regardless of the quantity in one country, whether a lot or a little will be sufficient for market needs in currency exchange, five: the dinar and dirham system will have stable exchange rates between countries